Intravenous remifentanil patient-controlled analgesia versus intramuscular pethidine for pain relief in labour (RESPITE): an open-label, multicentre, randomised controlled trial. Issue 10148 (25th August 2018) - Wilson, Matthew J A; MacArthur, Christine; Hewitt, Catherine A; Handley, Kelly; Gao, Fang; Beeson, Leanne; Daniels, Jane; ,
Summary: Background: About a third of women receiving pethidine for labour pain subsequently require an epidural, which provides effective pain relief but increases the risk of instrumental vaginal delivery. Remifentanil patient-controlled analgesia (PCA) in labour is an alternative to pethidine, but is not widely used. We aimed to evaluate epidural analgesia progression among women using remifentanil PCA compared with pethidine. Methods: We did an open-label, multicentre, randomised controlled trial in 14 UK maternity units. We included women aged 16 years or older, beyond 37 weeks' gestation, in labour with a singleton cephalic presentation, and who requested opioid pain relief. We randomly assigned eligible participants (1:1) to either the intravenous remifentanil PCA group (40 μg bolus on demand with a 2 min lockout) or the intramuscular pethidine group (100 mg every 4 h, up to 400 mg in 24 h), using a web-based or telephone randomisation service with a minimisation algorithm for parity, maternal age, ethnicity, and mode of labour onset. Because of the differences in routes of drug administration, study participants and health-care providers were not masked to the group allocation. The primary outcome was the proportion of women who received epidural analgesia after enrolment for pain relief in labour. Primary analyses were unadjusted and analysed by the intention-to-treat principle. This study is registered with the ISRCTN registry, number ISRCTN29654603. Findings: Between May 13, 2014, and Sept 2, 2016, 201 women were randomly assigned to the remifentanil PCA group and 200 to the pethidine group. One participant in the pethidine group withdrew consent, leaving 199 for analyses. The proportions of epidural conversion were 19% (39 of 201) in the remifentanil PCA group and 41% (81 of 199) in the pethidine group (risk ratio 0·48, 95% CI 0·34–0·66; p<0·0001). There were no serious adverse events or drug reactions directly attributable to either analgesic during the study. Interpretation: Intravenous remifentanil PCA halved the proportion of epidural conversions compared with intramuscular pethidine. This finding challenges routine pethidine use as standard of care in labour. Funding: National Institute for Health Research Clinician Scientist Award.